Model definitions to identify appropriate benchmarks in judiciary. Issue 1 (31st December 2022) - Falavigna, G.; Ippoliti, R.
ABSTRACT: In this manuscript we present a comparative analysis of benchmarks based on technical efficiency scores computed using Data Envelopment Analysis with two different model specifications. In one case, we adopt the number of settled cases as output and human resources as input; in the other case, we adopt the same model definition but with judicial expenditure as additional key input. Our findings show that the model specification containing both judicial expenditure and human resources is more appropriate than the model based only on human resources. Moreover, we show that, without considering the additional variable costs generated within the production process, those courts incorrectly identified as benchmarks might mislead the policy makers dealing with the reform process.